Strategi Organisasi untuk Memastikan Nilai Tambah Investasi Teknologi Informasi: Mitigasi Ketergantungan Merugikan melalui Alignment Strategis dan Manajemen Risiko - Silvi Andini; Muhammad Irwan Padli Nasution (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Investments in information technology (IT) often fail to deliver the expected added value due to excessive dependence on external suppliers, inflexible technological systems, or infrastructures that are highly vulnerable to various operational and security risks. This article analyzes organizational strategies to ensure the realization of added value from IT investments through the integration of strategic alignment and comprehensive risk management practices. By implementing strategic alignment, organizations are able to synchronize IT initiatives with core business objectives, organizational processes, and long-term strategic goals. At the same time, effective risk management plays a crucial role in reducing detrimental dependencies, including risks related to data breaches, system failures, cyber threats, and operational disruptions. This approach is supported by an extensive review of literature from credible and relevant academic sources, which demonstrates that systematic risk mitigation can significantly enhance organizational resilience, reliability, and overall value creation from IT investments. As a result, organizations are better positioned to optimize performance, improve decision-making capabilities, and ultimately achieve a sustainable competitive advantage in an increasingly digital business environment.